Pengaruh Pembelajaran Etnomatematika Permainan Marsitekka Terhadap Pemahaman Konsep Matematika Siswa Pada Materi Transformasi Geometri Kelas XI SMK Negeri 6 Medan T.A 2025/2026 - Septa Yesika Manurung; Agusmanto Hutauruk; Samuel Juliardi Sinaga (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study aims to determine the effect of ethnomathematics-based learning using the Marsitekka game on students’ mathematical conceptual understanding in geometry transformation material for Grade XI students at SMK Negeri 6 Medan. This research employed a quasi-experimental method with a population consisting of all Grade XI MPLB students, comprising three classes. The sample was determined through cluster random sampling, resulting in class XI MPLB 3 as the experimental class and class XI MPLB 1 as the control class. Data were collected using a conceptual understanding test. Data analysis included normality, homogeneity test, and t-test showed a difference in posttest scores of conceptual understanding between the two classes, with a significance value (Sig. 2-tailed) of 0,023, which is less than 0,05 at a 5% significance level. The average posttest score of the experimental class was 66.93, while the control class was 60,10, indicating that students’ mathematical conceptual understanding was in the good category. Based on the calculation of Effect Size (Cohen’s d), the value obtained was 0,603, which indicates that ethnomathematics learning through the Marsitekka game has a moderate effect on students’ mathematical conceptual understanding